Pencegahan Perilaku Bulliying pada Anak Usia Sekolah di SMP Nurul Khoir Kota Jambi: Pencegahan Perilaku Bulliying pada Anak Usia Sekolah di SMP Nurul Khoir Kota Jambi - Putri, Vevi Suryenti; Yanti, Rahmi Dwi; Suri, Marta (Jurnal Abdimas Kesehatan (JAK), 2025)
Cases of bullying that often occur in the world of education in Indonesia are increasingly concerning. The results of a study by the National Consortium for the Development of Character Schools in 2014 stated that almost every school in Indonesia had cases of bullying, even though it was only verbal and psychological/mental bullying. Cases of seniors bullying juniors keep popping up. The impact of bullying can threaten every party involved, both children who are bullied, children who are bullied, children who witness bullying, even schools with bullying issues as a whole. Bullying can have a bad influence on the physical and mental health of children. In severe cases, bullying can trigger fatal actions, such as suicide and so on. One of the places where bullying occurs is at school which is known as School bullying. School bullying is aggressive behavior that is carried out repeatedly by a person or group of students who have power, against other students who are weaker, with the aim of hurting that person, both physically and non-physically which can result in fear and trauma from the victim. An initial survey conducted at the Nurul Khoir Junior High School, Jambi City, through observation, found that some students played in groups/gangs and tended to mock each other among fellow students, especially the male group. Based on the results of interviews with the principal of SMP Nurul Khoir, teachers have never received guidelines for preventing bullying behavior at school and students have never been given education about bullying at school. The results of the activities carried out for 1 day showed an increase in students' knowledge about bullying behavior by 48%.